2018
DOI: 10.1002/er.4237
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid PV/T and Kalina cycle for power generation

Abstract: Summary This work introduces a novel hybrid system which uses the cooling water of a concentrated PV/T as a preheated water for lithium bromide‐water‐based Kalina cycle. The PV/T is a combination between solar photovoltaic cells and solar thermal collector. The solar cells convert the sunlight into electricity, and the remaining heat gets absorbed by the collector for additional power generation. As well as, extracting the excess heat from PV cells enhances its electrical efficiency. The Kalina power cycle is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Attaining solutions to such environmental problems that we face today, long-term planning and actions become vital for sustainable development [1]. Also, a large portion of the industry's research is heavily focused on advancements that reduce operational [7,8] or mending energy [9,10]. Besides, more importantly, renewable energy sources play a significant role in mitigating environment-related problems as they are environmentally friendly with affordable and competitive costs relative to conventional energy systems [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Attaining solutions to such environmental problems that we face today, long-term planning and actions become vital for sustainable development [1]. Also, a large portion of the industry's research is heavily focused on advancements that reduce operational [7,8] or mending energy [9,10]. Besides, more importantly, renewable energy sources play a significant role in mitigating environment-related problems as they are environmentally friendly with affordable and competitive costs relative to conventional energy systems [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the net present value (NPV) of a PV‐BES system with an optimized configuration is higher than the NPV of a PV system alone. Sharadga et al 22 presented a study on PV/T system which is a combination of solar photovoltaic cells and solar thermal collector. The hybrid system uses the cooling water of a concentrated PV/T as a preheated water for lithium bromide‐water‐based Kalina cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In their another study, Sharadga et al presented a novel hybrid system that uses the cooling water of a concentrated PV/T as a preheated water for lithium bromide‐water–based Kalina cycle. They declared that the electrical conversion efficiency of the proposed system is 40% to 68% much more compared with PV/T alone system . By pointing the importance of PV surface temperature, Bhattacharjee et al presented three new designs to decrease the panel temperature for absorbers places on the back of the PV in their experimental research.…”
Section: Introductionmentioning
confidence: 99%
“…They declared that the electrical conversion efficiency of the proposed system is 40% to 68% much more compared with PV/T alone system. 39 By pointing the importance of PV surface temperature, Bhattacharjee et al presented three new designs to decrease the panel temperature for absorbers places on the back of the PV in their experimental research. They indicated that the circular spiral semiflattened design absorber has the best results for the PV cooling.…”
Section: Introductionmentioning
confidence: 99%